Brasil: "mostra a tua cara"! Uma canção no tempo numa democracia em pauta - Cunha, Lázaro José de Medeiros (2022)
This work addresses the issue of the weakening of citizenship in the recent history of Brazil in the face of the scenario of questioning of the post-dictatorship democratic order, given the scenario of questioning the post-dictatorship democratic order, especially after 2013 when the process that resulted in the Impeachment/Coup of 2016 and the election of Jair Bolsonaro in 2018 began. From this reflection, the final product resulted in a didactic sequence, where I work exclusively with the song Brasil by Cazuza and its communication circuit. The activity is aimed at educators and students in Elementary School II, especially in the Ninth Year. In it, I explore music from its composition and release process, going through its repercussions and receptions, as well as its uses and appropriations today. Throughout the work, I develop reflections on our Educational Legislation for Elementary School II (DCN and BNCC) and its relationship with History Teaching, citizenship and democracy; as well as on the relationship between Music and History Teaching. Based on my academic research background (undergraduate and specialization) and my personal experiences as a musician and public school teacher, who always sought to explore Brazilian popular song as a historical source and didactic resource in History Teaching, I developed, throughout the dissertation, the construction of the final product. For this, I start my reflections on the current Brazilian context and the discussions of the present time, where democracy has been questioned and threatened, to return to the 1980s, when the country was emerging from a civil-military dictatorship and was undergoing a process of redemocratization, to analyze how the song Brasil, by Cazuza, released in 1987, has been re-signified over the years, including actually. With this, I aim, through the use of the Brazilian popular song in the classroom, to mediate students in order to identify changes and continuities, similarities and differences, between the repercussions of the song Brasil since the 1980s to the current context, relating the present and the past, by exploring the various meanings and uses of the song and the positions of its authors over time, in the sense of stimulating thinking historically, preparing them for life in a democratic regime, developing skills to observe, interpret, understand and think about the concepts and importance of citizenship and democracy and the civil, political and social rights nowadays.